2021
DOI: 10.1111/bph.15451
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in response to repeated intranasal oxytocin in schizophrenia and autism spectrum disorders: A meta‐analysis of variance

Abstract: Intranasal oxytocin (OT) has been suggested as a putative adjunctive treatment for patients with schizophrenia and autism spectrum disorders (ASD). Here, we examine available evidence from trials investigating the effects of repeated administrations of intranasal OT on the core symptoms of patients with schizophrenia and ASD, focusing on its therapeutic efficacy and heterogeneity of response (meta-analysis of variance). The repeated administration of intranasal OT does not improve most of the core symptoms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 100 publications
0
17
0
1
Order By: Relevance
“…Intranasal oxytocin, the most widely used method for oxytocin administration in humans, has been suggested as a promising therapeutic strategy for several brain disorders where we currently lack effective treatments (e.g., autism spectrum disorder 1 , schizophrenia 2 , migraine 3 , stroke 4 , obesity 5 , Prader-Willi 6 ). An increasing number of clinical trials have been evaluating the efficacy of specific nominal doses of intranasal oxytocin (for an overview see [7][8][9][10][11] ), yet most studies have been inconclusive at best 11,12 . The lack of unequivocal findings regarding the effects of intranasal oxytocin in trials with human patients contrasts with a flood of evidence showing consistent beneficial effects in animal models 13,14 , where oxytocin is often administered centrally [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Intranasal oxytocin, the most widely used method for oxytocin administration in humans, has been suggested as a promising therapeutic strategy for several brain disorders where we currently lack effective treatments (e.g., autism spectrum disorder 1 , schizophrenia 2 , migraine 3 , stroke 4 , obesity 5 , Prader-Willi 6 ). An increasing number of clinical trials have been evaluating the efficacy of specific nominal doses of intranasal oxytocin (for an overview see [7][8][9][10][11] ), yet most studies have been inconclusive at best 11,12 . The lack of unequivocal findings regarding the effects of intranasal oxytocin in trials with human patients contrasts with a flood of evidence showing consistent beneficial effects in animal models 13,14 , where oxytocin is often administered centrally [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis concluded that repeated administration of intranasal oxytocin had no effect on most core symptoms of schizophrenia, beyond a ‘small tentative effect’ on general symptoms [ 101 ]. However, looking at the heterogeneity in the responses to intranasal oxytocin, the authors suggested that there might be a subgroup of responsive patients.…”
Section: Partitioning the Citation Networkmentioning
confidence: 99%
“…Long-term exposure to high concentrations of oxytocin is hypothesized to downregulate the oxytocin-signaling machinery. It attenuates the oxytocinergic effect on brain function, and smaller improvements in the general symptoms of persons with schizophrenia have been reported [246], as demonstrated by the dampening of the response of the amygdala negatively affecting healthy volunteers who received daily intranasal oxytocin for 1 week compared with those who received single doses [247]. The mechanisms underpinning both schizophrenia and the oxytocinergic system have yet to be adequately characterized.…”
Section: The Implication Of Oxytocin In Schizophreniamentioning
confidence: 99%